Kinematics of the Final Approach and Take-Off Phases in World-Class Men and Women Pole Vaulters - Hanley, Brian; Gravestock, Helen J.; Hopkinson, Mike; Paradisis, Giorgos P.; Merlino, Stéphane; Bissas, Athanassios (Frontiers in Sports and Active Living, 2022)
The pole vault is a highly technical event where the athletes must successfully convert horizontal velocity during the run-up to vertical velocity at take-off. The aim of this study was to compare the kinematics of men's and women's world-class pole vaulting. Video data were collected of the best clearances by 14 men and 11 women at the 2018 IAAF World Indoor Championships using three high-speed cameras (200 Hz). Running velocity, step lengths, step times, and pole angles were measured during the run-up; during take-off, distance from the plant box, angle and velocity of take-off, and relative positions of the foot and hands were measured. Men achieved greater clearance heights with faster run-ups, faster take-off velocities and higher hand grip positions (all p < 0.001), with each of the last three steps longer for men when expressed as absolute values (all p < 0.001), but not when expressed relative to stature. There were no differences in run-up pole angles, step times, take-off angle, take-off contact time or time from pole plant to take-off. Women differed in their approach and take-off for characteristics affected by stature and strength, such as fewer run-up steps, shorter take-off distances, and lower grip heights. These lower grips result from a shorter, lighter pole, and this disadvantage was greater than slower run-up velocities. Coaches should therefore note that sex-based differences occur in the pole vault that result from anthropometric differences, but which do not negate the adoption of similar technical models of vaulting.